The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/1413-7054201943023418
|View full text |Cite
|
Sign up to set email alerts
|

Production of parsley in hydroponic conditions under isosmotic brackish nutrient solutions

Abstract: Brackish waters may vary in their chemical compositions, interfering with different plant responses to stress; therefore, the present study aimed to evaluate the production components of parsley plants subjected to levels of electrical conductivity in nutrient solutions with an initial ECns of 1.58 dS m-1, which was solubilized in water with the following water electrical conductivity configurations (ECw): 0.12 (control), 1.12, 2.12, 3.12, 4.12 and 5.12 dS m-1, resulting in six isosmotic levels (ECns = 1.7, 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Given this, any reduction in the SD, which is reflected in a decrease in the transpirational flux (e.g., [ 43 , 44 , 45 ]), may help the plant to avoid the potentially damaging effects of high ion concentrations in hydroponic systems. A number of studies have shown that plants cultivated in these systems are more able to adapt to conditions of high salinity than plants cultivated using conventional methods [ 46 ], which may reflect a potential for the use of brackish water, or even seawater in hydroponic systems (e.g., [ 47 , 48 , 49 , 50 ]). This adaptation may be related directly to the anatomical and physiological adjustments observed in the H. courbaril seedlings in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Given this, any reduction in the SD, which is reflected in a decrease in the transpirational flux (e.g., [ 43 , 44 , 45 ]), may help the plant to avoid the potentially damaging effects of high ion concentrations in hydroponic systems. A number of studies have shown that plants cultivated in these systems are more able to adapt to conditions of high salinity than plants cultivated using conventional methods [ 46 ], which may reflect a potential for the use of brackish water, or even seawater in hydroponic systems (e.g., [ 47 , 48 , 49 , 50 ]). This adaptation may be related directly to the anatomical and physiological adjustments observed in the H. courbaril seedlings in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The DFT system adapted to tubes has been used to cultivate different crops, such as coriander (Silva et al 2016b;Silva et al 2018;Silva et al 2020b), ornamental sunflower (Santos Júnior et al 2016bc;Souza et al 2020), lettuce (Cova et al 2017;Freitas al. 2021), bell pepper (Furtado et al 2017), rocket (Campos Júnior et al 2018, endive (Alves et al 2019a;Silva et al 2020a), basil (Alves et al 2019b;Azevedo Neto et al 2019;Gonçalves et al 2019;Alves et al 2021), chives (Silva Júnior et al 2019), and parsley (Martins et al 2019).…”
Section: Introductionmentioning
confidence: 99%